Brecha de género en la participación laboral y el tipo de unión conyugal en Argentina - Paz, Jorge A. (El Colegio de México A.C., 2021)
This article analyzes the possible effect of task division within households made up of united and married couples, on their levels and intensities of participation in the labor market. With data from the Time Use Module, added to the Annual Survey of Urban Households (2013), the following hypothesis is empirically explored: households made up of unmarried couples actually distribute domestic tasks (unpaid) more equally than households of married couples do, which leads to a more similar labor participation both in incidence and in intensity of participation. In other words, men and women who are members of the latter tend to be more specialized and, therefore, a gap of participation between genders is observed in these couples that is wider than that registered between men and women in fact united.